Traditional Jewelry of Uzbek Women-In World-Famous Museum Artifacts - Turaboyeva Yayra Rustamjonovna (Researchparks Publishing, 2023)
The article summarizes valuable information about artifacts that have become the gold reserves of world-famous museums of rare na'munas of traditional Uzbek women's jewelry, which are considered the NA'munas of material culture and art of Uzbekistan. In particular, the culture of our country, as a wealth of all mankind, is also described as a practical result of international cooperation efforts in the study of its national cultural heritage and its dissemination to the general public.